EXPLORING THE MACROECONOMIC DETERMINANTS OF REMITTANCES IN TOP REMITTANCES' RECIPIENT COUNTRIES - Ashfaque Ali Gilal; Hong Liu (JISR Management and Social Sciences & Economics)
This study aims to understand the  reasons  behind  remittances  sent  by emigrants working abroad. It focuses  on  the  top  ten  recipient  countries,  using data from the World Development Indicator (WDI) database  covering  1991  to 2022. Various econometric tests were conducted to analyze the data, including descriptive statistics,  correlation coefficients,  and unit root tests such as Breitung and Im Pesaran and Shin tests. Dynamic Ordinary  Least  Squares  (DOLS) and Panel ARDL models were used to explore long-term effects and relationships between macroeconomic variables and remittances. The findings indicate that remittances are motivated by both altruism and self-interest, showing both pro- cyclical and  counter-cyclical  patterns.  The  study  recommends  that  governments in these countries develop policies to encourage remittances through formal banking channels and registered money transfer services. It suggests implementing attractive incentives using modern technology and mobile apps, and enforcing strict measures against informal and illegal money transfer operations like hawala and hundi.